SYSTEM-CATEGORY ANALYSIS OF ECONOMIC UP-BRINGING PROBLEM IN PEDAGOGICAL SCIENCE - Akylbek Akhmetov (European Scientific Journal, ESJ, 2015)
The paper provides analysis of economic up-bringing in pedagogical science. Economic up-bringing with the necessity covers the formation of economic behavior. The total of a man’s deeds is expressed in his relationship with external economic environment, the system of personality economic activities, conscious, economically well-bred. Socially such behavior is stipulated by efficient economic activity in household activities, at school, in a society in general, in the process of household, socially useful productive labor. Crucial in behavior is the character of personality outlook, stipulating the direction, consequence and social-economic significance of this behavior. General personality economic qualities should find its implementation in it.